2002
DOI: 10.1111/j.1574-6941.2002.tb01011.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR primers for detection and characterisation of IncP-9 plasmids

Abstract: IncP-9 plasmids are best known as the vehicles for spreading biodegradation functions among Pseudomonas species but can also carry resistance determinants. New PCR primer systems targeting different replicon-specific regions were designed to allow detection of IncP-9 plasmids. Their specificity was checked against a range of IncP-9 plasmids as well as representatives of incompatibility groups IncFI, IncFII, IncN, IncQ, IncP-1alpha, IncP-1beta, IncP-2, IncP-7, IncP-13, IncW, IncU, IncX and IncZ. Products obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…When sequences of IncP-9 plasmids pMT2, pWW0, pDTG1 and NAH7 became available the relationships between them were estimated by sequence comparison and phylogenetic analysis (Dennis & Zylstra, 2004; Dennis, 2005; Greated & Thomas, 1999; Greated et al , 2002; Sota et al , 2006). PCR primers that target the basic replicon functions of IncP-9 have facilitated studies on the diversity and prevalence of naturally occurring IncP-9 plasmids (Greated & Thomas, 1999; Krasowiak et al , 2002). Thus, the genetic diversity of a limited number of phenotypically different IncP-9 plasmids (Krasowiak et al , 2002) and large collections of IncP-9 Nah replicons (Izmalkova et al , 2006; Leuchuk et al , 2006) have been evaluated by RFLP analysis of replication/maintenance loci, selected nah determinants or complete plasmid genomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When sequences of IncP-9 plasmids pMT2, pWW0, pDTG1 and NAH7 became available the relationships between them were estimated by sequence comparison and phylogenetic analysis (Dennis & Zylstra, 2004; Dennis, 2005; Greated & Thomas, 1999; Greated et al , 2002; Sota et al , 2006). PCR primers that target the basic replicon functions of IncP-9 have facilitated studies on the diversity and prevalence of naturally occurring IncP-9 plasmids (Greated & Thomas, 1999; Krasowiak et al , 2002). Thus, the genetic diversity of a limited number of phenotypically different IncP-9 plasmids (Krasowiak et al , 2002) and large collections of IncP-9 Nah replicons (Izmalkova et al , 2006; Leuchuk et al , 2006) have been evaluated by RFLP analysis of replication/maintenance loci, selected nah determinants or complete plasmid genomes.…”
Section: Introductionmentioning
confidence: 99%
“…PCR primers that target the basic replicon functions of IncP-9 have facilitated studies on the diversity and prevalence of naturally occurring IncP-9 plasmids (Greated & Thomas, 1999; Krasowiak et al , 2002). Thus, the genetic diversity of a limited number of phenotypically different IncP-9 plasmids (Krasowiak et al , 2002) and large collections of IncP-9 Nah replicons (Izmalkova et al , 2006; Leuchuk et al , 2006) have been evaluated by RFLP analysis of replication/maintenance loci, selected nah determinants or complete plasmid genomes. Environmental studies indicate a wide distribution of IncP-9-like replicons in manure, soils and coastal waters and their involvement in natural HGT of the naphthalene-degradation trait (Herrick et al , 1997; Krasowiak et al , 2002; Smalla et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although degradative and drug resistant plasmids from the plasmid families IncP-1, IncP-2, IncP-4 (IncQ), IncP-7 and IncP-9 are of obvious significance in different environments [2,5,6,10], little is known about the plasmid pool of marine ecosystems. Only a few studies revealed that 19%–30% of isolated seawater bacterial strains may carry plasmids [8,11,12].…”
Section: Resultsmentioning
confidence: 99%
“…, man-made chemical compounds is often encoded by IncP-1 representatives [1,3,4]. It has been shown also that the resistance to antibiotics in Pseudomonas species is associated with the IncP-9 plasmids [5,6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation